2004
DOI: 10.1038/sj.bmt.1704519
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus in long-term bone marrow transplant survivors

Abstract: Summary:The hepatitis C virus (HCV) infection may change the outcome of patients undergoing stem cell transplantation. This study aimed at determining the prevalence of the HCV antibody in patients who were alive 10 or more years after BMT, defining the annual progression rate of hepatic fibrosis in those patients, and identifying cases of cirrhosis among those who were positive for HCV antibody. Between 1979 and 1990, 259 patients had a bone marrow transplant, and 91 were alive in March 2000. Of those, 80 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
0
22
1
4
Order By: Relevance
“…A couple of long-term follow-up studies analyzing retrospectively the outcome of HCV-infected patients have been published. 3,4 Our study differs from the previously published studies by being prospective including a cohort of patients registered in the study between 1993 and 1996 and followed for 15 years. In addition, the study is significantly larger than the previously published studies both regarding the number of patients included and in the number of patients receiving antiviral therapy against HCV.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…A couple of long-term follow-up studies analyzing retrospectively the outcome of HCV-infected patients have been published. 3,4 Our study differs from the previously published studies by being prospective including a cohort of patients registered in the study between 1993 and 1996 and followed for 15 years. In addition, the study is significantly larger than the previously published studies both regarding the number of patients included and in the number of patients receiving antiviral therapy against HCV.…”
Section: Discussioncontrasting
confidence: 38%
“…In another small single-center study, 13.6% were reported to have liver cirrhosis. 4 The reported annual progression rate to severe complications in a large, retrospective study of HCV-infected individuals was 0.8% in patients who did receive antiviral therapy and 3.7% in patients without such therapy. 11 In an epidemiological review of patients with HCV, the reviewed information reported that 20% of patients would develop liver cirrhosis over a period of 20 --25 years 12 suggesting that our rate of 11.7% at 20 years after HSCT, and probably in many patients longer time since infection, does not represent a substantial difference compared with other nontransplanted HCV-infected populations.…”
Section: Discussionmentioning
confidence: 99%
“…Aetiology includes iron overload, 7,12,13 chronic viral hepatitis B and/ or C, 8,9,14 and chronic GVHD. 11 A few patients have autoimmune hepatitis and in some patients the cause of elevated liver enzymes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The World Health Organization (WHO) data suggests a worldwide prevalence of 2.2%-3.0%, with the highest prevalence found in the African and the Eastern Mediterranean regions. 10 Brazilian studies on this subject have been predominantly targeted risk groups [11][12][13][14] and blood donors. 15,16 Only few investigators have addressed the prevalence of hepatitis C in the general population or in minority groups.…”
Section: Introductionmentioning
confidence: 99%